2013
DOI: 10.1155/2013/878570
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Disorders among Secondary School Saudi Female Teachers

Abstract: Objective. This study was conducted to estimate prevalence and pattern of musculoskeletal pain disorders among secondary school Saudi female teachers in Al-Khobar area and the psychodemographic and psychosocial factors that may affect them. Material and Method. A cross-sectional study was conducted using sample of secondary schools teachers (governmental and private school) in Al-Khobar area, Saudi Arabia (KSA). Data were collected using a structured self-administered questionnaire. Result. Prevalence of muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
102
8
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(146 citation statements)
references
References 21 publications
23
102
8
13
Order By: Relevance
“…We could not find any researches comparing between male with female on back pain among high school teachers. In previous research, the subjective prevalence on back pain in females was approximately double than that in males [36]. This was different from our results.…”
Section: Discussioncontrasting
confidence: 99%
“…We could not find any researches comparing between male with female on back pain among high school teachers. In previous research, the subjective prevalence on back pain in females was approximately double than that in males [36]. This was different from our results.…”
Section: Discussioncontrasting
confidence: 99%
“…5 This study has revealed that female 78% and male 57.5% reported with the prevalence of LBP. Low back problem in the current study was more than that in Saudi 63.8%, 9 Botswana 55.7%, 14 Turkish teachers 74.9%, 11 Iranian teachers in a previous study 39 and in another Turkish study 51.4%, 31 China 40.0%, 26 France 34.8% 34 and Japan 20.6%. 43 The results of this part of study were relatively lower than Slovenian physical education 84.0%.…”
Section: Discussioncontrasting
confidence: 47%
“…Other studies have also found a high prevalence of absences due to musculoskeletal symptoms located in the same regions highlighted in this survey in basic education teachers 2,19,21 . Today, the teaching profession is regarded as one of the most stressful professions 26 .…”
Section: Discussionsupporting
confidence: 74%